2023
DOI: 10.3390/cancers15143577
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid PET/MRI in Cerebral Glioma: Current Status and Perspectives

Abstract: Advanced MRI methods and PET using radiolabelled amino acids provide valuable information, in addition to conventional MR imaging, for brain tumour diagnostics. These methods are particularly helpful in challenging situations such as the differentiation of malignant processes from benign lesions, the identification of non-enhancing glioma subregions, the differentiation of tumour progression from treatment-related changes, and the early assessment of responses to anticancer therapy. The debate over which of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 116 publications
0
9
0
Order By: Relevance
“…The present study reported that, although high-grade lesion may show heterogeneous conventional MRI features, in WHO grade 4 tumors herein, the level of MET uptake was higher, and ADC values were lower than in WHO grade 1 tumors, which agrees with previous studies. [25][26][27][28][29] Moreover, a meta-analysis focusing on glioma grading using 11 C-MET PET in adults found a sensitivity of 94% and a specificity of 89% to differentiate low-from high-grade glioma. 30 This clinical indication is underlined in the EANM/EANO/RANO guidelines for adult patients, 5 as a negative scan excludes a grade 3/4 glioma, but it can also exclude a lymphoma or metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The present study reported that, although high-grade lesion may show heterogeneous conventional MRI features, in WHO grade 4 tumors herein, the level of MET uptake was higher, and ADC values were lower than in WHO grade 1 tumors, which agrees with previous studies. [25][26][27][28][29] Moreover, a meta-analysis focusing on glioma grading using 11 C-MET PET in adults found a sensitivity of 94% and a specificity of 89% to differentiate low-from high-grade glioma. 30 This clinical indication is underlined in the EANM/EANO/RANO guidelines for adult patients, 5 as a negative scan excludes a grade 3/4 glioma, but it can also exclude a lymphoma or metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Combined 11 C-MET PET and MRI is used in brain tumors to perform targeted biopsies and to define the tumor limit 8,17 ; the complementary information provided by MRI and PET parameters in pediatric brain tumors was assessed by a limited number of studies, and none used MET. 7,18,31 Herein, the MET uptake was compared with the ADC min , which is used as a marker of dense tissue with high cellularity, small extracellular space, and high nuclear/cytoplasmic ratio.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations